Introduction of the harmonised respiratory physiotherapy curriculum. Issue 2 (June 2019) - Troosters, Thierry; Tabin, Nathalie; Langer, Daniel; Burtin, Chris; Chatwin, Michelle; Clini, Enrico M.; Emtner, Margareta; Gosselink, Rik; Grant, Kathleen; Inal-Ince, Deniz; Lewko, Agnieszka; Main, Eleanor; et al.
Building on the core syllabus for postgraduate training in respiratory physiotherapy, published in 2014, the European Respiratory Society (ERS) respiratory physiotherapy task force has developed a harmonised and structured postgraduate curriculum for respiratory physiotherapy training. The curriculum outlines the knowledge, skills and attitudes which must be mastered by a respiratory physiotherapist working with adult or paediatric patients, together with guidance for minimal clinical exposures, and forms of learning and assessment. This article presents the rationale, methodology and content of the ERS respiratory physiotherapy curriculum. The full curriculum can be found in thesupplementary material . The respiratory physiotherapy curriculum describes the knowledge, skills and attitudes that must be mastered by a respiratory physiotherapist working with adults and/or children.  http://bit.ly/2Do7Vll